2021
DOI: 10.7595/management.fon.2021.0034
|View full text |Cite
|
Sign up to set email alerts
|

Does the Achievement of Gender Equality in Society Reflect on Gender Issues in Corporate Governance: The Case of the West Balkan's Banking Sector?

Abstract: Driven by the idea that women do not realize their full potential in society based on not being equally paid, having lower education level than men and facing discrimination based on maternity leave have been a primary motivation to do the research on the following sources of data: HDI; GDI and GII indexes published for four West Balkan countries and average data of women on boards for the same countries experienced in the most developed and female-dominated industry such as banking. This idea helps us formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The relationship between age diversity and firm performance, borrowing cost, dividend policy, and earnings management was part of numerous studies as well (Ferrero-Ferrero et al, 2015;Waheed & Malik, 2019;Algatan, 2019;Knežević et al, 2021;Arenas-Torres et al, 2021;Marzuki et al, 2019).…”
Section: Theoretical Foundations Of the Researchmentioning
confidence: 99%
“…The relationship between age diversity and firm performance, borrowing cost, dividend policy, and earnings management was part of numerous studies as well (Ferrero-Ferrero et al, 2015;Waheed & Malik, 2019;Algatan, 2019;Knežević et al, 2021;Arenas-Torres et al, 2021;Marzuki et al, 2019).…”
Section: Theoretical Foundations Of the Researchmentioning
confidence: 99%
“…The banking sector is particularly suitable for gender analysis in the Balkan region as the banking industry is generally not male-dominated. In the Balkan region, women make up most of the graduated students of the faculties of economics, which is why they contribute more to the gender structure of the bank's employees (Knežević, Pavlović and Bojičić, 2022;Knežević, Pavlović and Arıç, 2021). Therefore, women in managerial positions in the banking sector were not an isolated case in the former Yugoslavia either.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the labor mobility particularly intense between the bank executives, the management of banks is correspondingly largely gender-balanced. Knežević, Pavlović, and Bojičić (2022) recently demonstrated that different level of gender equality in the societies of the Balkan region does not reflect on gender issues in corporate governance of the banking sector.…”
Section: Introductionmentioning
confidence: 99%